Analisis Kelayakan Finansial Usaha Ternak Kambing Etawa Senduro Di Kecamatan Senduro Kabupaten Lumajang - Puspita, Salsabila Ika; Widayanti, Sri; Yektiningsih, Endang (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2024)
Indonesia is known to have many types of livestock and natural resources, one of which is goats. Senduro District is one of the leading goat farming centers. Indicators of the success of the livestock business include the size of the financial aspect. Goat farming business needs to be equipped or accompanied by relevant data information for financial feasibility analysis. The purpose of this study was to analyze the feasibility of the goat farming business in Senduro to determine whether the business being run is profitable or not using NPV, IRR, and BEP assessment criteria because farmers tend to trade their livestock businesses without analyzing their business feasibility. The population in this study is Senduro etawa goat farmers totaling 12 breeders. This research uses financial service analysis methods with assessment criteria, namely BEP, IRR, NPV. The NPV results of the etawa Senduro goat farming business located in Lumajang Regency, especially in Kandang Tepus Village, show that the business is feasible to run, because it produces NPV of Rp 1,617,311,892 and more than 0. The IRR result of the goat farming business in Kandang Tepus Village, Senduro District is also said to be feasible because the IRR yield is 30.15%, this result exceeds the loan interest of 15%. BEP in the goat farming business in Senduro can be said to be feasible or profitable because the average BEP unit in this business is 54 heads and the revenue of this business is IDR 2,298,050,000.